Upregulation of HLA Class I Expression on Tumor Cells by the Anti-EGFR Antibody Nimotuzumab - Garrido, Greta; Rabasa, Ailem; Garrido, Cristina; Chao, Lisset; Garrido, Federico; García-Lora, Ángel M.; Sánchez-Ramírez, Belinda (Frontiers in Pharmacology, 2017)
Defining how epidermal growth factor receptor (EGFR)-targeting therapies influence the immune response is essential to increase their clinical efficacy. A growing emphasis is being placed on immune regulator genes that govern tumor - T cell interactions. Previous studies showed an increase in HLA class I cell surface expression in tumor cell lines treated with anti-EGFR agents. In particular, earlier studies of the anti-EGFR blocking antibody cetuximab, have suggested that increased tumor expression of HLA class I is associated with positive clinical response. We investigated the effect of another commercially available anti-EGFR antibody Nimotuzumab on HLA class I expression in tumor cell lines. We observed, for the first time, that nimotuzumab increases HLA class I expression and its effect is associated with a coordinated increase in mRNA levels of the principal antigen processing and presentation components. Moreover, using 7A7 (a specific surrogate antibody against murine EGFR), we obtained results suggesting the importance of the increased MHC-I expression induced by EGFR-targeted therapies display higher in antitumor immune response. 7A7 therapy induced upregulation of tumor MHC-I expression in vivo and tumors treated with this antibody display higher susceptibility to CD8+ T cells-mediated lysis. Our results represent the first evidence suggesting the importance of the adaptive immunity in nimotuzumab-mediated antitumor activity. More experiments should be conducted in order to elucidate the relevance of this mechanism in cancer patients. This novel immune-related antitumor mechanism mediated by nimotuzumab opens new perspectives for their combination with various immunotherapeutic agents and cancer vaccines.